Optimization of building envelope design for nZEBs in Mediterranean climate: Performance analysis of residential case study. (1st December 2016) - Ascione, Fabrizio; De Masi, Rosa Francesca; de Rossi, Filippo; Ruggiero, Silvia; Vanoli, Giuseppe Peter
Highlights: Dynamic simulation tool and multi-objective optimization algorithm are combined. Design criteria for residential nZEB in Mediterranean climate are discussed. Passive strategies for opaque and transparent building envelope are compared. PCM, cool roof, different walls' and window technologies, shading systems are examined. Minimization of energy demand is studied, by assuming discomfort as constraint. Abstract: Design criteria for a residential nZEB in Mediterranean climate are discussed. The integrated design procedure focuses on the problem of a large number of available building variants concerning the building envelope. The aim is to search the ones that minimize winter and summer energy demand without compromising thermal comfort. The adopted methodological approach combines the use of dynamic energy simulation tool (EnergyPlus), based on a one-dimensional conduction finite difference solution method, and a constrained multi-objective optimization algorithm. For four cities (Madrid, Nice, Naples, Athens), several passive strategies are compared: thermal properties of the building envelope, adoption of phase change materials with different melting temperatures, cool roof solutions, several window/wall ratio values, some external and internal shading systems. The results allow to evidence that it is difficult to understand the best trade-off between summer and winter performance, by assuring high standard of thermal comfort when the aim is to reach NZEB objectives in Mediterranean climate. However, some guidelines are indicated, starting from the discussed results.